Bridging Nutrition and Dentistry: An Interprofessional Education (IPE) Experience Model - Noorullah K; Oshita SE; McNeil AT; Ijaz A; Iqbal L; Tomar SL; Smith PD; Bilal S (Journal of Multidisciplinary Healthcare)
Khatija Noorullah,1 Shayna Emily Oshita,2 Amy T McNeil,2 Anum Ijaz,3 Laila Iqbal,1 Scott L Tomar,1 Patrick Dean Smith,1 Sobia Bilal1 1Division of Prevention and Public Health, College of Dentistry, University of Illinois Chicago, Chicago, IL, USA; 2Kinesiology and Nutrition, University of Illinois Chicago, Chicago, IL, USA; 3Division of Epidemiology and Global Health, School of Public Health, University of Illinois at Chicago, Chicago, IL, USACorrespondence: Sobia Bilal, Division of Prevention and Public Health, College of Dentistry, University of Illinois Chicago, 801 S. Paulina St, Chicago, IL, 60612, USA, Email sbilal@uic.eduPurpose: Interprofessional Education (IPE) is essential for fostering collaborative healthcare practices. The purpose of this paper is to share a detailed description of the design, development process, implementation, and planned evaluation of an IPE model connecting Nutrition and Dentistry programs at the University of Illinois Chicago (UIC). The program sought to address educational gaps and enhance collaborative learning among healthcare students.Methods: This IPE teaching activity was guided by the World Health Organization’s IPE guidelines and the Core Competencies for Interprofessional Collaborative Practice. The process involved the formulation of educational model, preparation of students and implementation of three IPE sessions as a collaborative effort between dental and nutrition faculty. Teaching strategies included small group discussions and case studies to foster inclusive learning. The IPE teaching activity evaluation presented in this article corresponds to traditional pretest-posttest (TPP) design, using a validated IPE tool SPICE-R2. Qualitative reflective feedback was collected to understand the program’s impact on professional confidence and holistic care delivery. Quantitative analysis was conducted using T-test for pre and post SPICE-R2 scores and thematic analysis to analyze the qualitative reflections.Results: Pre and post SPICE-R2 scores analysis showed significant improvements in overall students’. For the domains of interprofessional teamwork, understanding of roles, and patient care outcomes, high significance was noted. Qualitative feedback highlighted the program’s success in enhancing professional confidence and promoting patient-centered care. Students valued the diverse and dynamic teaching strategies employed. Challenges included space limitations and initial role clarification difficulties.Conclusion: This IPE model effectively improved students’ perception towards interprofessional collaborative teamwork, roles and patient outcomes. Recommendations for future iterations include expanding the program to multiple institutions, varied learning environments, and long-term assessments to ensure sustained impact. These findings underscore the importance of Interprofessional Education in preparing healthcare professionals for collaborative practice and improving patient care outcomes.Keywords: interprofessional education, curriculum development, dietary counseling, nutrition, dentistry, undergraduate dental education